Initial presenting symptoms and severity of SARS-CoV-2 Wild type, the Delta variant and the Omicron variant infected cases in early fourth wave of epidemics in Myanmar - Pyar, Khin Phyu; Su, Khine Khine; Wunna, Kyaw; Aung, Zar Ni Htet; Maung, Nyan Lin; Kyaw, Aung Phyoe; Hlaing, Soe Win; Tun, Thi Han; Htun, San Myint; Aung, Nay Myo; Than, Aye Min; Mon, Min Kyi; et al. (Jour Med Resh and Health Sci, 2022)
The “severe acute respiratory syndrome coronavirus type 2” (SARSCoV-2) is also known as “coronavirus disease 19” (COVID-19). It originated in Wuhan, Hubei province, People’s Republic of China, in December 2019; and, it spread worldwide causing a global pandemic. Genetic variants of SARS-CoV-2 have been emerging and circulating around the world throughout the COVID-19 pandemic till 2022: original (wild-type), Alpha, Beta, Delta, and Gamma. In third wave, the notorious variant was the Delta variant; it was well-known for quick transmissibility, causing high morbidity and mortality. In late November, the Omicron variant was first detected in South Africa. Therefore, evidences are required about the transmissibility and virulence among several variants and old Wild type.